Low substrate temperature deposition of transparent and conducting ZnO:Al thin films by RF magnetron sputtering. (April 2016) - Waykar, Ravindra; Amit, Pawbake; Kulkarni, Rupali; Jadhavar, Ashok; Funde, Adinath; Waman, Vaishali; Dewan, Rupesh; Pathan, Habib; Jadkar, Sandesh
Abstract: Transparent and conducting Al-doped ZnO (ZnO:Al) films were prepared on glass substrate using the RF sputtering method at different substrate temperatures from room temperature (RT) to 200 °C. The structural, morphological, electrical and optical properties of these films were investigated using a variety of characterization techniques such as low angle XRD, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), field-emission scanning electron microscopy (FE-SEM), Hall measurement and UV–visible spectroscopy. The electrical properties showed that films deposited at RT have the lowest resistivity and it increases with an increase in the substrate temperature whereas carrier mobility and concentration decrease with an increase in substrate temperature. Low angle XRD and Raman spectroscopy analysis reavealed that films are highly crystalline with a hexagonal wurtzite structure and a preferred orientation along the c -axis. The FE-SEM analysis showed that the surface morphology of films is strongly dependent on the substrate temperature. The band gap decreases from 3.36 to 3.29 eV as the substrate temperature is increased from RT to 200 °C. The fundamental absorption edge in the UV region shifts towards a longer wavelength with an increase in substrate temperature and be attributed to the Burstein-Moss shift. The synthesized films showed an average transmission (> 85%) in the visible region, which signifies that synthesized ZnO:Al films can be suitable for display devices and solar cells as transparent electrodes.